Kontribusi Power Otot Tungkai dan Koordinasi Mata dan Kaki Terhadap Keterampilan Sooting Sepakbola Pada Club FC Bentra Benyah - Rohmadani, Rohmadani; Henjilito, Raffly (Institut Teknologi Pendidikan Indonesia, 2023)
Eye and Foot Coordination of Football Shooting Skills at Club FC Bentra Benayah. This type of research is correlational research, namely a statistical tool, which can be used to compare the measurement results of two or more different variables to determine the level of relationship between these variables. The population is all research subjects, the population in this study is all players at Club FC Bentra Benayah totaling 18 people. The sample for this study used a total sampling technique, meaning that the entire population was sampled. So the number of samples in this study was 18 men. Based on the analysis of the data obtained a) There is a Power contribution to the Shooting skills of Club FC Bentra Benayah by 22.74%. seen from the value of r count (0.477) > r table (0.468). b)There is a contribution of eye and foot coordinationto the Shooting skills of Club FC Bentra Benayah by 27.39%. seen from the value of r count (0.523) > r table (0.468). c)There is a contribution of Power and eye and foot coordination to the Shooting skills of Club FC Bentra Benayah by 28.11%.seen from the value of r count (0.530) > r table (0.468).